GE_GERICHTE P/7955/2011 vom 14. Oktober 2011 - GE Cour de justice (2011)
; PRINCIPE DE LA CÉLÉRITÉ ; DÉTENTION PROVISOIRE ; PROLONGATION ; OBSERVATION DU DÉLAI ; FRAIS DE LA PROCÉDURE | CPP.227; CPP.5; CPP.428